Histamine in psychiatry: promethazine as a sedative anticholinergic. (17th April 2019) - Cookson, John
SUMMARY: The author reflects on discoveries over the course of a century concerning histamine as a potent chemical signal and neurotransmitter, the development of antihistamines, including promethazine, and chlorpromazine from a common precursor, and the recognition of a major brain pathway involving histamine. Although chlorpromazine has been succeeded by numerous other antipsychotics, promethazine remains the antihistamine recommended for sedation in acutely disturbed patients, largely because it is potently anticholinergic at atropinic muscarinic receptors and therefore anti-Parkinsonian: this means it is also useful in combination with older antipsychotics such as haloperidol. DECLARATION OF INTEREST: None.